Impacts of the Deepwater Horizon oil spill on the salt marsh vegetation of Louisiana. (September 2016) - Hester, Mark W.; Willis, Jonathan M.; Rouhani, Shahrokh; Steinhoff, Marla A.; Baker, Mary C.
Abstract: The coastal wetland vegetation component of the Deepwater Horizon oil spill Natural Resource Damage Assessment documented significant injury to the plant production and health of Louisiana salt marshes exposed to oiling. Specifically, marsh sites experiencing trace or greater vertical oiling of plant tissues displayed reductions in cover and peak standing crop relative to reference (no oiling), particularly in the marsh edge zone, for the majority of this four year study. Similarly, elevated chlorosis of plant tissue, as estimated by a vegetation health index, was detected for marsh sites with trace or greater vertical oiling in the first two years of the study. Key environmental factors, such as hydrologic regime, elevation, and soil characteristics, were generally similar across plant oiling classes (including reference), indicating that the observed injury to plant production and health was the result of plant oiling and not potential differences in environmental setting. Although fewer significant impacts to plant production and health were detected in the latter years of the study, this is due in part to decreased sample size occurring as a result of erosion (shoreline retreat) and resultant loss of plots, and should not be misconstrued as indicating full recovery of the ecosystem. Graphical abstract: Highlights: Deepwater Horizon oiling impacts on LA salt marsh vegetation were assessed. Plant oiling reduced LA salt marsh vegetation health and productivity metrics. Injury to vegetation was most pronounced in the marsh edge. Vegetation impacts were less detectable after 3 years, largely due to plot erosion. Abstract : Capsule: A geographically-extensive field study revealed that salt marsh vegetation oiled by the Deepwater Horizon oil spill displayed reductions in vegetation production and health metrics.